Evaluation of Pseudomonas fluorescens Strains, Fungicides and Non-conventional Chemicals Against Botyrotinia ricini Causing Grey Mold Disease in Castor - Basha, S. Ameer; Ramya, V.; Begum, A. Sajeli; Raghavendra, G.; Ramanjaneyulu, A. V.; Nagesh Kumar, M. V. (International Journal of Bio-resource and Stress Management, 2021)
A study was made to evaluate the efficacy of Pseudomonas fluorescens strains, fungicides and non-conventional chemicals against Botryotinia ricini, causing grey mold disease in castor, under in vitro conditions. Among the 40 strains isolated from rhizosphere soil samples of different crops across the State of Telangana, India, only eight strains inhibited the growth of B. ricini under dual culture technique, of which strains Pf 21 (90.56%), Pf 23 (88.89%), Pf 34 (86.11%) and Pf 36 (84.17%) were the most effective. Among the seven chemicals (four fungicides and three non-conventional chemicals) tested for their efficacy, carbendazim followed by propiconazole had significant antagonistic effect against B. ricini. Exposure of healthy castor capsules to B. ricini and P. fluorescens for different time periods revealed that strains Pf 34 and Pf 36 were effective in completely inhibiting the growth of B. ricini and hence these two strains have been identified as effective biocontrol agents, on par with carbendazim, which offer scope for sustainable and integrated disease management of grey mold disease in castor.